Multiplex PCR testing requires a robust multi-disciplinary strategy to effectively manage identified cases of chlamydial conjunctivitis. Issue 2 (May 2013) - Lockington, D; MacDonald, R; King, S; Weir, C; Winter, A; Aitken, C
Introduction: Implementation of an in-house polymerase chain reaction (PCR) multiplex assay by West of Scotland Specialist Virology Centre to improve sample processing means all viral eye swabs are now routinely tested for Adenovirus, Herpes simplex, Varicella and Chlamydia . Concern was raised regarding subsequent management and sexual health attendance for Chlamydia -positive patients identified in eye casualty. Methods: A retrospective review of virology results identified 76 Chlamydia -positive patients from 1914 eye swabs (4%) from May 2007 to April 2008. Of these results, 12 originated from Glasgow eye casualty and available clinical notes were cross-referenced with the sexual health network (Sandyford). Results: Identified issues included no documentation of implications of testing, poor communication of positive results and poor referral pathways to sexual health for assessment; all leading to inadequate management. A shared care network was created to address these issues. A designated sexual health advisor was identified to improve sexual health referral, specialist assessment, standardised management and contact tracing. Re-audit showed more consistent follow-up. Conclusion: New PCR technology has resulted in a shared care approach to address corresponding implications of testing. Effective communication with a structured protocol and a central point of contact has improved follow-up and ensures appropriate best practice management of chlamydial conjunctivitis.